"A Fine Line That We Walk Every Day": Self-Care Approaches Used by Family Caregivers of Persons with Dementia. (4th March 2019) - Anderson, Joel G.; Hundt, Elizabeth; Dean, Morgan; Rose, Karen M.
Abstract: Individuals living with Alzheimer's disease and related dementias (ADRD) often exhibit behavioral and psychological symptoms of distress that can contribute to the strain experienced by their family caregivers. This strain can increase levels of stress for family caregivers and reduce quality of life, which can have a negative impact on physical health and wellbeing for both the caregiver and the person with ADRD. This study used blogs written by family caregivers of persons with ADRD to explore self-care strategies practiced by these caregivers. Using a qualitative thematic analysis, seven themes related to self-care approaches used by caregivers of persons with ADRD were identified: (1) health and wellness; (2) altruism and activism; (3) reminiscing and legacy building; (4) social support; (5) information exchange; (6) organization and planning; and (7) spirituality. By understanding the ways in which caregivers for someone with ADRD practice self-care, interventions and services can be developed in an effort to improve caregiver quality of life.